Super computing in engineering analysis - Adeli, Hojjat (New generation computing, 1992)
The first volume in this new series has a companion in volume 2 (unseen), Parallel processing in computational mechanics . The first six contributions present general aspects of supercomputing from both hardware and software engineering points of view. Subsequent chapters discuss homotopy algorithms.